AI Agent Based Service Innovation to Enhance Efficiency and User Experience - Cahyono, Dwi; Atmaja, Hanung Eka; Zainarthur, Henry (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
The innovation of services based on Artificial Intelligence (AI) Agent has become a key strategy in improving operational efficiency, service quality, and user experience across various digital business sectors. AI Agent, utilizing natural language processing, machine learning, and realtime data analysis, can automate service processes that previously required manual interaction, such as customer responses, recommendations, and processing complex information. This study aims to analyze how the application of AI Agent can accelerate service responses, improve information accuracy, and create more personalized interactions for users. The research method used is a literature review from reputable journals, academic books, and industry reports, which are then analyzed descriptively to identify the adoption patterns of AI Agent across various digital platforms such as e-commerce, financial services, education, and creative industries. The results of the literature synthesis show that AI Agent can reduce operational workload by up to 40%, accelerate service response time by up to 60%, and enhance user satisfaction through adaptive interactions tailored to individual preferences and behaviors. Additionally, the implementation of AI Agent also proves to improve service consistency, expand operational scalability, and reduce the risk of human error in service processes. These findings emphasize that the integration of AI Agent not only enhances the efficiency and effective- ness of digital business processes but also plays a key role in creating strategic innovation, strengthening competitiveness, and building a more responsive and valuable service experience for users in the digital era.